Multiple sets resistance training: Effects of condensed versus circuit models on muscular strength, endurance and body composition - Arazi, H.; Asadi, A (Journal of Human Sport & Exercise, 2013)
The purpose of this study was to examine the effects of condensed multiple-set resistance training and circuit multiple-set resistance training on muscular strength, endurance, body composition and arm and thigh circumference in healthy males. Twenty seven healthy males volunteered to participate in this study and assigned into three groups; according to; condensed multiple-set group (COM; n=9), circuit multiple-set group (CIM; n=8) and control group (CON; n=10). Subjects in the COM performed resistance training exercises for 3 sets continuously; whereas subjects in the CIM performed resistance training program for 1 set of each exercise and come back to the first exercise and this approach was performed 3 times each training session. Pre and post 8 weeks of training, one repetition maximum (1RM) and muscle endurance (60% of 1RM) for leg press and bench press, body weight, arm and thigh circumference and body composition were measured. No significant differences in body mass, arm and thigh circumference and muscular strength for the bench press exercise were observed for any group during the 8 weeks of training period (p > 0.05). A significant increase in muscular strength for the leg press exercise was observed for COM after 8 weeks of training (p < 0.05). Both the COM and CIM groups showed significant improvement compared with pre training and CON in muscular endurance for the bench press and leg press exercises (p < 0.05). In conclusion, it can be recommended that, COM is better for improving muscle strength and both training programs are proper for increasing muscular endurance.